Effects of sugar concentration, natural ventilation and supporting materials on the growth of in vitro strawberry plantlets (Fragaria ananassa Duch.) and on the survival rate of ex vitro plantlets - Tri, Nguyen Minh; Quynh, Nguyen Thi (Academia Journal of Biology, 2014)
The growth of strawberry (Fragaria ananassa Duch.) plantlets cultured in vitro as affected by sugar, types of supporting material and number of air exchange of the vessel was investigated. Shoots of in vitro strawberry plantlets were cultured on the on full strength MS (Murashige & Skoog 1962) basal liquid medium with 30 g/l sugar and without sugar. Two types of supporting material, agar and florialite, and two levels of air exchange expressed by number of air exchange per vessel, 0.3 and 2.3 per hour, were studied. At the end of a 35-day culture period, fresh weight, dry weight, leaf area, number of leaves, chlorophyll content, photosynthetic net rate of plantlets grown on florialite soaked in sugar-free medium and under the higher number of air exchanges were greater than those in sugar-containing medium. The survival rate of ex vitro plantlets cultured under a high number of air exchange and supporting with florialite was also the highest (98%) among SA, SF, FA and FF treatments.